2007
DOI: 10.3346/jkms.2007.22.s.s24
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the RUNX3 Gene by Promoter Hypermethylation and Hemizygous Deletion in Breast Cancer

Abstract: The RUNX3 gene is regarded as a tumor suppressor gene in many human solid tumors, and its inactivation is believed to be related with solid tumor carcinogenesis. As little information is available about the role of the RUNX3 gene in breast cancer, we investigated the relationship between the RUNX3 gene and breast cancer. We performed reverse transcriptase-polymerases chain reaction (RT-PCR), methylation specific PCR, and bicolor fluorescent in situ hybridization analysis in an effort to reveal related mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…RUNX3 methylation correlated with inactivated protein expression in 93% ( n = 31) of neoplastic samples. The methylation frequencies of RUNX3 in DCIS and IDC, although relatively higher, are comparable to previously published reports (52%, n = 44 31 ; 86.7%, n = 15 45 ; 52.6%, n = 19 46 ; 22%, n = 37 36 ; 25%, n = 25 35 ). Besides promoter methylation, mislocalization of RUNX3 from the nucleus to cytoplasm was also detected in a significant proportion of DCIS (80%, n = 20) and IDC (85%, n = 20), suggesting an alternative mechanism of RUNX3 inactivation independent of promoter methylation, a finding consistent with our previous studies in gastric cancers, 34 colorectal polyps 41 and adenocarcinomas, 38 hepatic (unpublished data) and breast cancers, 31,37 wherein we demonstrated that RUNX3 when present in the cytoplasm is in an inactive state.…”
Section: Discussionsupporting
confidence: 90%
“…RUNX3 methylation correlated with inactivated protein expression in 93% ( n = 31) of neoplastic samples. The methylation frequencies of RUNX3 in DCIS and IDC, although relatively higher, are comparable to previously published reports (52%, n = 44 31 ; 86.7%, n = 15 45 ; 52.6%, n = 19 46 ; 22%, n = 37 36 ; 25%, n = 25 35 ). Besides promoter methylation, mislocalization of RUNX3 from the nucleus to cytoplasm was also detected in a significant proportion of DCIS (80%, n = 20) and IDC (85%, n = 20), suggesting an alternative mechanism of RUNX3 inactivation independent of promoter methylation, a finding consistent with our previous studies in gastric cancers, 34 colorectal polyps 41 and adenocarcinomas, 38 hepatic (unpublished data) and breast cancers, 31,37 wherein we demonstrated that RUNX3 when present in the cytoplasm is in an inactive state.…”
Section: Discussionsupporting
confidence: 90%
“…A higher methylation frequency is found in another study with 52% of breast cancer samples (n=44) and 50% of breast cancer cell lines (n=19) showing Runx3 promoter hypermethylation [Lau et al, 2006]. In a separate study, Hwang et al showed a similar frequency of hypermethylation of the Runx3 promoter in 53% of breast cancer tissues (n=40) and in 57% of breast cancer cell lines (n=13) [Hwang et al, 2007]. …”
Section: Inactivation Of Runx3 By Promoter Hypermethylation In Breastmentioning
confidence: 84%
“…A role for RUNX3 as a tumor suppressor in breast cancer emerged when its inactivation was seen in many breast cancer cell lines and breast cancer tissues. Like in other cancers, RUNX3 is inactivated in breast cancer by reduced copy number, promoter hypermethylation, hemizygous deletion, and protein mislocalization [Chen et al, 2007; Hwang et al, 2007; Jiang et al, 2008; Lau et al, 2006; Subramaniam et al, 2009a]. RUNX3 inactivation is considered to be an early event in breast cancer progression, and its expression generally decreases during this process [Subramaniam et al, 2009a].…”
Section: Introductionmentioning
confidence: 99%
“…The RUNX3 promoter is hypermethylated in many cancers, including those of the lung, liver, colon, bladder, breast, and testis Xiao and Liu, 2004;Goel et al, 2004;Kim et al, 2005;Hwang et al, 2007;Kato et al, 2003;Lind et al, 2006). Interestingly, Kato and colleagues reported that while 8 of 10 infantile yolk sac tumors exhibited RUNX3 hypermethylation (specimens obtained from pediatric patients), 0 of 12 adult nonseminomatous TGCTs contained methylated RUNX3, despite 7 of the 11 mixed/combined TGCTs containing yolk sac tumors (Kato et al, 2003).…”
Section: Runx3mentioning
confidence: 99%